Pengaruh Kecerdasan Emosional, Pola Asuh Demokratis, dan Kecerdasan Interpersonal Terhadap Sikap Remaja - Andi Patimbangi (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2018)
The aim of this study was to determine the effect of emotional intelligence, democratic parenting, and interpersonal intelligence of adolescent attitudes regarding free sex. The researcher used ex post facto method. The polulation was all students of MAN 1 Kajuara Bone Regency. While sample taken random sampling technique. The resercher used Structural Equation Modeling (SEM), namely AMOS program which has the aim to test a series of relationships "complicated" simultaneously. The results showed that emotional intelligence and interpersonal intelligence of student MAN 3 Bone were good category, while parenting applied by parents of MAN 3 Bone students were quite democratic. Furthermore, based on hypothesis testing found that both exogenous variables namely emotional intelligence and influential democratic parenting significant effect on adolescent attitudes regarding free sex. Interpersonal intelligence reinforces both the influence of these exogenous variables. The researcher also found that adolescents who are emotionally intelligent, educated with a democratic pattern and have good interpersonal intelligence tend to view that free sex is a form of negative behavior that must be avoided and away from the trigger that can plunge teenagers into behavior. Key words: Emotional Intelligence, Democratic Parenting, Interpersonal Attitud